2021
DOI: 10.1051/parasite/2021011
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal transcriptomes in Kazakh sheep with different haplotypes after experimentalEchinococcus granulosusinfection

Abstract: Cystic echinococcosis (CE) is a chronic zoonosis caused by infection with the larval stage of the cestode Echinococcus granulosus. As the intermediate host, sheep are highly susceptible to this disease. Our previous studies have shown that sheep with haplotype MHC Mva Ibc-Sac IIab-Hin1I ab were resistant to CE infection, while their counterparts without this haplotype were not. In order to reveal the molecular mechanism of resistance in Kazakh sheep, after selecting the differential miRNA in our previous study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
1
4
1
Order By: Relevance
“…It's reported that the orally-infected E. granulosus tightly installed in the intestine of dog, thereby establishing strong adhesion to crypts and impairing the intestinal mucus integrity (33). Additionally, the parasite can damage the epithelial tissue barrier, then penetrate and migrate to other organs in the Kazakh sheep (22). In the present study, we observed that intraperitoneally EgPSC infection reduces the colon length and cecum size of mice.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…It's reported that the orally-infected E. granulosus tightly installed in the intestine of dog, thereby establishing strong adhesion to crypts and impairing the intestinal mucus integrity (33). Additionally, the parasite can damage the epithelial tissue barrier, then penetrate and migrate to other organs in the Kazakh sheep (22). In the present study, we observed that intraperitoneally EgPSC infection reduces the colon length and cecum size of mice.…”
Section: Discussionsupporting
confidence: 59%
“…studies have recognized the relationship between intestinal immune-related genes expression and CE (42). For example, Kazakh sheep with E. granulosus infection were found higher expression level of lectins receptors in intestines, facilitating the capability to respond and eliminate orally acquired E. granulosus (22). Here, we found that intraperitoneally EgPSC-infected mice show lower expression level of Stat4 and IL12rb1.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations